Retrospect and Prospect of Existing Problems and Scientific Planning in Macau Marine Space - YANG Jing; SHUI Bing; NI Mingxuan (Renmin Zhujiang)
The Macao Special Administrative Region is located at the outlet of the Pearl River.It is a typical beach land.It has expanded from 2.78 km2 in 1840 to more than 32 km2 at present.All the land is reclaimed from the sea.It is one of the regions with the highest proportion of land reclamation in the world.By reviewing the history of land reclamation in Macao Special Administrative Region,examining the current situation of water quality and excavating the existing problems of sea area development,this paper puts forward that it is necessary to establish a unified administrative structure in charge,strengthen pollution control,improve rain and sewage diversion treatment and discharge capacity,establish a pollution discharge permit system,promote regional legal cooperation and linkage law enforcement,and build a data platform.To achieve multi-party data fusion and other measures,so as to realize the advance planning of the sea area and scientific decision-making,so as to generate into the sea,improve the disaster resistance capacity of flood control and moisture-proof in the Macao Special Administrative Region,and better serve the development of the sea area and diversified economic construction of the Macao Special Administrative Region.